Building strong music programs a handbook for preservice and novice music teachers - Ryan, Charlene, 1971- (Rowman & Littlefield Education, 2009)
Building Strong Music Programs uniquely focuses on music programs in the public school community, providing strategies and tools for developing a vibrant music program and building community support. Covering relationships with colleagues, parents, staff, administrators, and the community at large, Charlene Ryan also provides tactics for developing courses, performances, and publicity to enhance your program. Build a repertoire of tried-and-true strategies covering curriculum, classroom management, special needs, concerts, assessment, budget, and more that are based on years of teaching at all l.